The Effect Analysis of Liquidity, Solvency on Profitability and Its Impact to the Company Value at PT KS, Tbk - Masno Marjohan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
he purpose of this study is to analyze the company's ability to pay short-term debt and long-term debt, and this study is also to determine the effect on profitability and its impact on the firm value of the manufacturing industry listed on the Indonesia Stock Exchange (Tbk). The data is obtained from the company's annual reports from 2009 to 2018. The research method used by the author is quantitative descriptive method, by analyzing financial reports with quantitative data obtained from the company's official website and the Indonesia Stock Exchange. Management of statistical data usingEviews.The result of the research is to get the influence between variable X1, variable Y and X2 with variable Y, and simultaneously and variable Y to variable Z (Company value) by using multiple linear analysis obtained a regression equation. Calculation of the coefficient of determination or R Square, This shows that Liquidity (Current Ratio) and Solvency (Debt to Asset Ratio) have an influence on Profotability (Return on Assets) while the rest is influenced by other variables. Partially the liquidity variable (Current Ratio) has a significant influence on Profitability (Return on Assets), while partially there is an insignificant effect of Debt to Asset Ratio on Profitability (Return on Assets).